Risk Factors for Obesity in Five-Year-Old Children: Based on Korean National Health Insurance Service (NHIS) Data - Mi Jin Choi; Hyunju Kang; Jimi Choi (MDPI AG, 2022)
This study aimed to identify the risk factors for obesity in five-year-old children using data from the database of the Korean National Health Insurance Service. We identified 26,047 children who underwent the sixth screening (at age 5) from the 2017 National Health Screening Program for Infant and Children and for whom data from the fourth screening (at age 3) database and the mothers' health screening and eligibility database were available. To identify the risk factors of obesity, odds ratios and 95% confidence intervals were calculated by a hierarchical multiple logistic regression. Female sex, a birth weight of over 4 kg, the "caution/refer" remark during developmental screening at ages three and five, maternal obesity, and a middle-level income were risk factors for obesity in the subjects. Good appetite, high consumption of milk, heavy intake of sweet food at age three, speedy eating, irregular meals and snack times, large single-meal quantities, heavy intake of oily and salty food, and not performing physical exercise at age five were also considered significant risk factors. For early intervention efforts to prevent childhood obesity, modifiable behavioral factors and other obesity risk factors identified in this study could be used to target high-risk children and dietary behaviors.